ANALYSIS OF BEGINNING TEACHER TEACHING PROGRAM IN INCREASING THE PROFESSIONALISM COMPETENCE OF MADRASAH IBTIDAIYAH TEACHER EDUCATION IBN KHALDUN UNIVERSITY ALUMNI IN PRIMARY EDUCATION - Salati Asmahasanah; Oking Setia Priatna (Universitas Muhammadiyah Ponorogo, 2018)
The purpose of this study is, the first to analyze the implementation of mentoring programs for beginner teachers who are alumni of Madrasah Ibtidaiyah Teacher Education Ibn Khaldun University who have worked in basic education institutions in the city of Bogor. Second, it describes the influence of the mentoring program on improving the professional competence of beginner teachers. Third, good communication and kinship between alumni and alma mater is established. The research method used is mix methods (qualitative and quantitative). Data collection in this study uses interviews, observation, focus group discussions, and scale. The object of this research is Madrasah Ibtidaiyah Teacher Education Ibn Khaldun University alumni who work in Bogor in different basic education institutions, namely public elementary schools, Private Madrasah Ibtidaiyah and Islamic Elementary School, which are honorary and permanent teachers. The conclusion of the result of this study is the Madrasah Ibtidaiyah Teacher Education Ibn Khaldun University alumni assistance program is proven to improve teacher professionalism competencies which include six indicators, those are the application of science, work productivity, innovation, problem solving, work environment adaptation, responsiveness of students' needs. And tighten the fabric of communication between alumni and nature.